BEAUTY VLOGGER FIANI ADILAA DAN PEMBENTUKAN NARASI KECANTIKAN - Pradita Rahmalia, Yossy; Purwo Saputro, Edy (Linimasa : Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the role of Fiani Adilaa, an Indonesian beauty vlogger, in shaping perceptions of beauty standards among Communication Studies students at Universitas Muhammadiyah Surakarta. Using a descriptive qualitative approach, data were collected through in-depth interviews with five students who actively follow Fiani Adilaa's content. The findings reveal that Fiani Adilaa's content not only delivers beauty tutorials and product reviews but also constructs an inclusive narrative of beauty through the promotion of self-love and self-acceptance. These messages influence audiences to perceive beauty as personal and authentic, reducing societal pressure to conform to narrow beauty standards. However, the study also identifies the dual influence of social media, which simultaneously reinforces idealized beauty standards while creating space for more realistic perspectives. This research highlights the potential of beauty vloggers as agents of change in broadening societal views on beauty, particularly in the context of digital mass communication. These findings provide a foundation for further studies on the influence of social media in shaping societal constructs of beauty standards.